Proceedings of the 2018 International Seminar on Education Research and Social Science (ISERSS 2018) 2018
DOI: 10.2991/iserss-18.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Evaluation of EFL Students' Critical Thinking Dispositions in Digital Learning

Abstract: Abstract-EFL college students acquire knowledge in the digital learning environment. Fostering critical thinking dispositions in digital learning is of great importance. This crosssectional study aims to explore the impact of digital learning on EFL college students' critical thinking dispositions. This study invites 64 EFL students from Z University and conducts the Chinese version of Critical Thinking Disposition Inventory (CTDI-CV) and semi-interviews for measurements. It finds out that digital learning imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Therefore, schools are supposed to organize training programs to equip teachers with important ICT knowledge and sufficient ICT skills as well as provide in-time technical support once teachers encounter any difficulty in using ICT in class and so forth (Hadi and Zeinab, 2012). In this case, teachers would be able to use ICT as cognitive tools in class, contributing to an ideal technology-assisted learning environment (e.g., Kommers et al, 2001; Nissen and Tea, 2012; Wei and Hu, 2018; Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, schools are supposed to organize training programs to equip teachers with important ICT knowledge and sufficient ICT skills as well as provide in-time technical support once teachers encounter any difficulty in using ICT in class and so forth (Hadi and Zeinab, 2012). In this case, teachers would be able to use ICT as cognitive tools in class, contributing to an ideal technology-assisted learning environment (e.g., Kommers et al, 2001; Nissen and Tea, 2012; Wei and Hu, 2018; Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…"Based on the theory of connectivism, educators take an essential role in digital learning." (Wei & Hu, 2018)…”
Section: "It Is Important To Reflect On Concepts Such As Open Educatimentioning
confidence: 99%
“…In this study, in schools where principals managed to motivate teachers to improve teaching quality, students performed better in PISA 2015 test. A number of studies indicated that the leadership role of the principal was more important than other contextual factors in school, which contributed to students' achievement (Ho & Lau, 2018;Shin, Slater, & Ortiz, 2017;Wei & Hu, 2018a). Teacher participation (LEADTCH) referred to principals offering opportunities to teachers to manage school affairs.…”
Section: School-level Factors Related To Students' Reading Literacymentioning
confidence: 99%